The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 2014 Conference on Internet Measurement Conference 2014
DOI: 10.1145/2663716.2663750
|View full text |Cite
|
Sign up to set email alerts
|

A Look at the Consequences of Internet Censorship Through an ISP Lens

Abstract: Internet censorship artificially changes the dynamics of resource production and consumption, affecting a range of stakeholders that include end users, service providers, and content providers. We analyze two large-scale censorship events in Pakistan: blocking of pornographic content in 2011 and of YouTube in 2012. Using traffic datasets collected at home and SOHO networks before and after the censorship events, we: a) quantify the demand for blocked content, b) illuminate challenges encountered by service pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 12 publications
(10 reference statements)
0
28
0
Order By: Relevance
“…Social media in particular stands out, consistent with external evidence that this is increasingly seen as a threat by censors [23]. Blocking access to video-sharing and other entertainment sites may also be meant to suppress copyright infringement and/or support local businesses over global incumbents [37].…”
Section: Topic Correlationsmentioning
confidence: 59%
See 2 more Smart Citations
“…Social media in particular stands out, consistent with external evidence that this is increasingly seen as a threat by censors [23]. Blocking access to video-sharing and other entertainment sites may also be meant to suppress copyright infringement and/or support local businesses over global incumbents [37].…”
Section: Topic Correlationsmentioning
confidence: 59%
“…In some cases, it has been possible to identify the specific "filter" in use [20,34]. Another line aims to understand what is censored and why [1], how that changes over time [3,28], how the degree of censorship might vary within a country [68], and how people react to censorship [37,38].…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In another instance, a hacktivist group leaked 600 gigabytes of log files of Internet filtering devices used in Syria, allowing researchers to gain insights into censorship in that country [27]. Similarly, an anonymous ISP in Pakistan provided researchers access to a trove of data that enabled analysis of Pakistani censorship [28].…”
Section: Background Technical Backgroundmentioning
confidence: 99%
“…The results showed that in both events a significant increase in encrypted traffic occurred shortly after the imposition of the censorship. Additionally, a notable drop in the use of the local DNS resolvers arose, indicating that different anti-censorship techniques were employed [19].…”
Section: Literature Reviewmentioning
confidence: 99%